Firewood Dependency and the Shift to Biogas in Rural Nepal: Evidence from Koshi Province - Laxmi Kanta Sharma; Arjun Kumar Baral (Journal of Development and Administrative Studies, 2025)
Firewood remains the predominant household energy source in rural Nepal, particularly in Koshi Province, where it poses significant economic, health, and environmental burdens. This study, based on empirical data from 240 households, quantifies firewood consumption patterns and associated impacts while assessing the viability of transitioning to biogas systems. The results indicate that households consume an average of 14977.44 kg of firewood annually, contributing to the felling of 20–30 trees per year and emitting 18.5 tons of CO2 per household. Women and children spend approximately 386.88 hours per year on firewood collection, and indoor air pollution affects 60% of households, contributing to respiratory illnesses and other health concerns (WHO, 2022). The study finds biogas systems can reduce firewood use by up to 90% and significantly improve health outcomes and economic conditions. However, barriers such as upfront costs, limited infrastructure, and low awareness hinder adoption. This paper offers detailed policy recommendations to address these barriers and support sustainable energy transition aligned with Nepal's SDG commitments.